Use of mangiferin as a non-drug phytotherapy strategy in the treatment of type 2 diabetes mellitus: an integrative review (Research, Society and Development, 2022)
Mangifera Indica Linn is the scientific name for the popularly known mango, and this plant contains many beneficial properties for health. Humans are able to use its leaves, extract, trunk bark, because it contains an active substance named mangiferin which has numerous medicinal properties. As it is a natural and low-cost product for consumers, it can be a complementary herbal medicine strategy for several pathologies, including Type 2 Diabetes Mellitus (DM2). Mangiferin has several properties as antioxidant, antidiabetic, anticancer, anti-inflammatory, antitumor, antiviral, anthelmintic, antibacterial, antihypertensive, among other chronic non-communicable diseases. General objective: describe the main findings in the literature about the use of the herbal medicine of mangiferin in the prevention and/or treatment of DM2. Methodology: an integrative review was adopted, through the PICO strategy, including research in Portuguese and English available in several scientific databases on the platforms: Scielo, PubMed, Sciencedirect. Results: data obtained from literature suggest the use of mangiferin as a prophylactic strategy in the auxiliary treatment of DM2, which can enhance the reduction in the consumption of industrialized drugs, as well as in the prevention of diseases. Conclusion: through the integrative review, it was possible to identify that mangiferin demonstrates a great potential in the treatment not only of DM2, as well as in other chronic non-communicable diseases.